Balancing between livelihood and biodiversity conservation: a model study on gear selectivity for harvesting small indigenous fishes in southern Bangladesh. Issue 2 (3rd April 2018) - Islam, Mohammad Mahmudul; Islam, Naimul; Mostafiz, Md.; Sunny, Atiqur Rahman; Keus, Hendrik Jan; Karim, Manjurul; Hossain, Mohammed Zakir; Sarker, Subrata
Abstract: This study has determined a suitable mesh size for small indigenous fish species (SIS) harvesting and has also developed a new gill net operation technique taking into consideration of aquatic biodiversity conservation, the daily intake of micro-nutrients and the livelihood of the rural community. A total of 60 household women involved in mola carplet ( Amblypharyngodon mola ) culturing participated in this study. We e used mola catch data obtained from harvesting operations of two different durations. Mola harvesting was carried out twice a day at two sites for a period of 180 days using three different mesh-size nets. Mesh size, duration and timing (time of the day) of the harvesting operation were found to be important factors determining mola catches. Among the three mesh size nets used for mola fishing, the 0.70 inch mesh size net proved to be the most suitable... This mesh size net exhibits high efficiency in catching mola, the catch rate of small indigenous non-target fish being lower, and thus contributes to the aquatic diversity conservation. This study provides an insight into how employment of specialized fishing gear can help balance SIS fishing as a source of the rural community's livelihood against biodiversity conservation.